Nilai Ekonomi Air Domestik dan Irigasi Pertanian: Studi Kasus di Desa-Desa Sekitar Kawasan Taman Nasional Gunung Halimun - Widada; Darusman, Dudung (Institut Pertanian Bogor (IPB University), 2004)
The hydrological function of Gunung Halimun National Park (GHNP) has enormous benefit for local people. To predict the monetary benefit of water stemming from the park, the research was conducted by taking 13 representative samples of villages surrounding GHNP. Through the economic valuation, this research found out that the total economic value (TEV) water was Rp 6.64 billion per year, consisting of water value for domestic uses (Rp 5.22 billion), and water value for agriculture uses (Rp 1.42 billion). The TEV of the water equal to Rp 6.64 billion (Rp 173.278,47 per ha) is representing economic benefit value of water stemming from area TNGH for the community of 51 villages which abut on direct by TNGH. The monetary value certainly will be bigger if we look at the area broader as the all area of watershed function. The enormous benefit value of water (domestic and the agriculture) prove that development of conservation area (in this case is GHNP) do not oppose against economic development.